2019
DOI: 10.15244/pjoes/87139
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Study on the Development of Green Agriculture in China Based on Ambidexterity Theory Perspective

Abstract: Since the initiation of reform and opening up policy in the late 1970s, agriculture has developed rapidly in China, producing substantial economic benefits while being accompanied by grievous pollution and food safety issues mainly due to the immoderate use of fertilizer and pesticide [1, 2]. More specifically, the amount of fertilizer application to land use in 1978 was 8.84 million tons, which has grown to 60.23 million tons in 2015, with approximately five times of net increase [3]. The pesticides and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Cui et al constructed evolutionary game models between the government and farmers, farmers and agricultural enterprises, to attempt to obtain the best stable strategy for better green technology diffusion. Their results indicated that slashing green production costs and supervision cost of government were crucial for the best stable strategy [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cui et al constructed evolutionary game models between the government and farmers, farmers and agricultural enterprises, to attempt to obtain the best stable strategy for better green technology diffusion. Their results indicated that slashing green production costs and supervision cost of government were crucial for the best stable strategy [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their study, they used evolutionary game theory to unpack the interactive strategies of the polluting enterprise, local government regulators, and central government planners. Cui et al studied the green agriculture game through building an evolutionary game between the government and the farmer [17].…”
Section: Introductionmentioning
confidence: 99%
“…7e dynamic game process is a mixed strategy game and the diversification of strategy selection. Under certain probability conditions, the game process is adjusted according to the strategy of the other one [42]. 8As AI enterprises, their technical threshold is very high.…”
Section: Assumptionsmentioning
confidence: 99%